Entrepreneurship based on local wisdom: exploring the meaning of Pangadereng in MSME business practices in Bone regency, South Sulawesi - Burhanuddin (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines how pangadereng—a moral–cultural system grounded in honor, etiquette, reciprocity, and religious ethics—continues to shape entrepreneurial behavior among micro, small, and medium enterprises (MSMEs) in Bone Regency, South Sulawesi. Using a qualitative phenomenological design involving interviews, participant observation, and artifact analysis, the research explores how entrepreneurs interpret and operationalize pangadereng amid digitalization, market integration, and shifting generational norms. Findings show that pangadereng structures trust, informal credit, reputation repair, price negotiation, and conflict resolution, functioning as an embedded governance mechanism that reduces uncertainty and sustains long-term exchange relationships. However, while these relational strengths support resilience and survival, they also limit scalability due to constrained access to formal finance, uneven digital capability, and tensions between moral profitability and competitive pressure. The study argues that pangadereng is an adaptive rather than static system, with younger entrepreneurs selectively reinterpreting its values in digital contexts. Policy implications include the need for culturally attuned business training, reputation-based microfinance models, gender-responsive support mechanisms, and co-designed digital tools that preserve soft information flows essential to trust-based markets. The study concludes by positioning pangadereng as a strategic cultural asset that can anchor inclusive and ethically grounded entrepreneurial development when integrated with modern competencies and institutional support.